2015
DOI: 10.15294/jdm.v6i2.4302
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attitude in Mediating Consumer Knowledge Influence Towards the Purchase Intention of Green Product

Abstract: Protecting the environment has become a main idea for some modern companies in applying the green marketing strategy. Many consumers perceive that a product with natural raw material can give a better benefit both in terms of health issue and environment. The purpose of this study is to find out the role of attitude in mediating consumer knowledge influence towards the purchase intention of green product Ever-E 250 in Denpasar.The samples were 110 respondents from all over Denpasar taken with the purposive sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 4 publications
1
16
0
2
Order By: Relevance
“…Furthermore, according to Hair et al (2010) if a and b are significant, but c is not significant, then Attitude towards green products is expressed as perfect mediation. Based on the result, Environmental Knowledge has proven to have a significant influence on Attitude, this result is in line with several previous studies (Smith & Paladino, 2010;Wulandari et al, 2015;Saichao, 2016). Mostafa (2007) found that knowledge about environmental problems is an important factor that influences the attitudes of the consumers in Egypt to be more environmentally friendly.…”
Section: Descriptive Statisticssupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, according to Hair et al (2010) if a and b are significant, but c is not significant, then Attitude towards green products is expressed as perfect mediation. Based on the result, Environmental Knowledge has proven to have a significant influence on Attitude, this result is in line with several previous studies (Smith & Paladino, 2010;Wulandari et al, 2015;Saichao, 2016). Mostafa (2007) found that knowledge about environmental problems is an important factor that influences the attitudes of the consumers in Egypt to be more environmentally friendly.…”
Section: Descriptive Statisticssupporting
confidence: 91%
“…Chen & Chai (2010) define attitudes as manifestations of someone's likes or dislikes and attitudes to responding to various environmental problems are a reflection of how much someone wants to be involved in environmental preservation. Environmental Knowledge has proven to have a significant influence on Attitude, this is evident in several studies (Smith & Paladino, 2010;Wulandari et al, 2015;Saichao, 2016). Based on the results of previous studies, the author would like to further confirm the relationship between Environmental Knowledge and Attitude in the hypothesis as follows:…”
Section: Research Hypothesesmentioning
confidence: 93%
“…Subjective Knowledge positively and also significantly affects the Product attitude (Paladino and Ng, 2012). Therefore, based on previous studies (Paladino and Ng, 2012;Chen, 2013;Wulandari, Rahyuda & Yasa, 2015;Nordin & Ahmad. 2013;Peschel et al, 2016), this study hypothesized that Subjective Knowledge has a positive and significant effect on Product Attitude.…”
Section: Relationship Between Objective Knowledge and Environmental Attitudementioning
confidence: 96%
“…In addition, an individual who is favorable with counterfeits perceives the quality of counterfeit goods to be as good as the original goods (Norum & Cuno, 2011), so when the counterfeit luxury goods are not same as the original products, consumers do not really have the intention to purchase it (Chiu & Leng, 2015;Wulandari et al, 2015;Hashim et al, 2018). We assumed that the closer the difference of the quality between original luxury goods and counterfeit luxury goods which means that the higher the quality of counterfeit luxury goods is the higher the intention to purchase the counterfeit luxury goods.…”
Section: Relationship Between Quality and Intention To Purchasementioning
confidence: 99%